Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(\tan^2\alpha\left(2\cos^2\alpha+\sin^2\alpha-1\right)\)
\(=\tan^2\alpha\left(\cos^2\alpha+\cos^2\alpha+\sin^2\alpha-1\right)\)
\(=\tan^2\alpha\left(\cos^2\alpha+1-1\right)\)
\(=\tan^2\alpha.\cos^2\alpha=1\)
b, \(\sin\alpha-\sin\alpha.\cos^2\alpha\)
\(=\sin\alpha\left(1-\cos^2\alpha\right)\)
\(=\sin\alpha.\sin^2\alpha\)
bn ơi lm j có công thức \(\tan^2a\times\cos^2a=1\) đâu
a)sin a-sin a.cos^2 a=sin a(1-cos^2 a)=sin a(sin^2 a)=sin^3 a
b)sin^4a+cos^4a+2sin^2acos^2a=(sin^2a+cos^2a)^2=1^2=1
\(=\frac{\sin^2a}{\sin a-\cos a}-\frac{\sin a+\cos a}{\frac{\sin^2a}{\cos^2a}-1}=\)
\(=\frac{\sin^2a}{\sin a-\cos a}-\frac{\cos^2a\left(\sin a+\cos a\right)}{\sin^2a-\cos^2a}=\)
\(=\frac{\sin^2a\left(\sin a+\cos a\right)-\cos^2a\left(\sin a+\cos a\right)}{\sin^2a-\cos^2a}=\)
\(=\frac{\left(\sin a+\cos a\right)\left(\sin^2a-\cos^2a\right)}{\sin^2a-\cos^2a}=\sin a+\cos a\left(dpcm\right)\)
a. \(\dfrac{1+2sin\alpha cos\alpha}{cos^2\alpha-sin^2\alpha}=\dfrac{sin^2\alpha+2sin\alpha cos\alpha+cos^2}{\left(cos\alpha-sin\alpha\right)\left(cos\alpha+sin\alpha\right)}=\dfrac{\left(sin\alpha+cos\alpha\right)^2}{\left(cos\alpha-sin\alpha\right)\left(cos\alpha+sin\alpha\right)}=\dfrac{sin\alpha+cos\alpha}{cos\alpha-sin\alpha}\)
~ ~ ~ Áp dụng đẳng thức \(\left(a+b\right)^2+\left(a-b\right)^2=2\left(a^2+b^2\right)\) ~ ~ ~
a)
\(\left(\sin\alpha+\cos\alpha\right)^2-2\sin\alpha\cos\alpha-1\)
\(=\left(\sin\alpha+\cos\alpha\right)^2-\left(2\sin\alpha\cos\alpha+\sin^2\alpha+\cos^2\alpha\right)\)
\(=\left(\sin\alpha+\cos\alpha\right)^2-\left(\sin\alpha+\cos\alpha\right)^2\)
= 0
b)
\(\left(\sin\alpha-\cos\alpha\right)^2+2\sin\alpha\cos\alpha+1\)
\(=\left(\sin\alpha-\cos\alpha\right)^2+2\sin\alpha\cos\alpha+\sin^2\alpha+\cos^2\alpha\)
\(=\left(\sin\alpha-\cos\alpha\right)^2+\left(\sin\alpha+\cos\alpha\right)^2\)
\(=2\left(\sin^2\alpha+\cos^2\alpha\right)\)
= 2
c)
\(\left(\sin\alpha+\cos\alpha\right)^2+\left(\sin\alpha-\cos\alpha\right)^2+2\)
\(=2\left(\sin^2\alpha+\cos^2\alpha\right)+2\)
= 4
d)
\(\sin^2\alpha\cot^2\alpha+\cos^2\alpha\tan^2\alpha\)
\(=\left(\sin\times\dfrac{\cos}{\sin}\right)^2+\left(\cos\times\dfrac{\sin}{\cos}\right)^2\)
= 1
=\(\frac{sin^2a-2sina.cosa+cos^2a}{\left(sina-cosa\right)\left(sina+cosa\right)}=\frac{\left(sina-cosa\right)^2}{\left(sina-cosa\right)\left(sina+cosa\right)}=\frac{sina-cosa}{sina+cosa}=\frac{tana-1}{tana+1}\)